2013
DOI: 10.7567/jjap.52.116501
|View full text |Cite
|
Sign up to set email alerts
|

Fluidic Self-Assembly Using Molten Ga Bumps and Its Application to Resonant Tunneling Diodes

Abstract: Fluidic self-assembly (FSA) using molten metal bumps is one of the most promising heterogeneous integration (HI) technologies, which enable us to integrate devices made of various materials on various substrates. We can fabricate the metal bumps using Ga having diameters of 24, 18, 12, and 8 µm with good yield. Using Ga has significant advantages; especially, it includes no toxic metals. These bumps were used for the FSA process of the metal dummy blocks having a diameter of 18 µm, and a good yield of 84% was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…So far, most of the self-assembly works have dealt with highly symmetric square, polygonal, circular, or low-aspect-ratio rectangular chips. 10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Broesch et al have reported the effects of chip geometries on restoring force and torque by extending the symmetric squares to rectangles with high aspect ratios using simulation software. 38) However, only a few papers on liquid-mediated self-assembly even with symmetric square chips have described their alignment accuracies in detail.…”
Section: Optical Interconnectionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most of the self-assembly works have dealt with highly symmetric square, polygonal, circular, or low-aspect-ratio rectangular chips. 10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Broesch et al have reported the effects of chip geometries on restoring force and torque by extending the symmetric squares to rectangles with high aspect ratios using simulation software. 38) However, only a few papers on liquid-mediated self-assembly even with symmetric square chips have described their alignment accuracies in detail.…”
Section: Optical Interconnectionmentioning
confidence: 99%
“…18) In that technique, trapezoidal GaAs light-emitting diodes (LEDs) are self-assembled into anisotropically etched pockets formed on Si substrates by gravitational force with shape and size reorganization. Many groups have reported on self-assembly with small optical devices such as LEDs, 19) laser diodes (LDs), 20) vertical-cavity surface-emitting lasers (VCSELs), 21) Si mirrors, 22) thin-film photodetectors, 23) SiO 2 plates, 24) and resonant tunneling diodes, 25) which are 10-900 µm on one side. Geometrical shape recognition with unidirectional or convectional liquid flows 18,20,21,25) and surface tension (capillary forces) 19,[22][23][24] are utilized as a driving force to self-align the microparts and microstructures.…”
Section: Introductionmentioning
confidence: 99%